Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

InsanelyChaotic

  • 3 years ago

Solve the systems using substitution. 6x + 2y = 0 4x + y = -1

  • This Question is Closed
  1. Luigi0210
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Solve the second equation for y: y=-4x-1 Then plug it in to the other equation: 6x+2(-4x-1)=0 6x-8x-2=0 -2x=2 x=-1 Plug in x and solve for y. 4x+y=-1 4(-1)+y=-1 -4+y=-1 y=3

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy